Pero Budmani’s four letters to Hugo Schuchardt - Ligorio Orsat L. (Južnoslovenski Filolog)
In 1899 and 1900, Pero Budmani, the then editor of the Dictionary of the Yugoslav Academy (Rečnik JAZU), wrote four letters to Hugo Schuchardt, a renowned German scholar specializing in Romance languages and Basque. Their correspondence has recently been digitized within the Schuchardt Archives at the University of Graz. These letters discuss the meaning and origins of the Serbo-Croatian piscatorial term trbok and even offer a valuable insight into Budmani’s interest in Dalmatian-Romance loanwords. Budmani was the first scholar to study this subject; in his paper Dialect of Dubrovnik, as it is Spoken Today (Dubrovački dijalekat, kako se sada govori) (1883), he identified the first loanwords of Dalmatian-Romance origin in Serbo-Croatian (60 of them, to be precise). From one of the letters to Schuchardt, it can be inferred that he later intended to publish another study on the subject – a project which never came to fruition. For this purpose, he gathered about sixty Dalmatian-Romance loanwords in total, including those he already published in the Dialect of Dubrovnik. The paper concludes that the newly collected Dalmatian-Romance loanwords (not more than 10 in number) must have been the ones that Budmani identified while editing the letter K for the Dictionary of the Yugoslav Academy, i.e., SCr. kentènār ‘silk thread, string’, kȅra ‘tuft’, kìjerna ‘Cerna gigas’ and kìmenat ‘crack between two boards on a ship’, to which may be added SCr. gȅra ‘Smaris alcedo’, specifically designated as a Dalmatian-Romance loanword in one of Budmani’s letters to Schuchardt.